Factors that lead physicians to initiate and maintain relationships with credit unions: a case study - Unicred Fortaleza - Pedro Jorge Fernandes Pinto (2007)
The high inflationary indices that had lasted in Brazil in the 80âs, had been damaging, for several segments of the society, benefiting few economic sectors. Among those segments that had grown in this uncommon conjuncture, the financial institutions are distinguished, companies that focused their activities in terms of keeping public founds and application from federal governmentâs papers, avoiding to carry through operations of loans and financings, preventing to run in risk. The management used to maximize profits and to prevent risks took these institutions to carry through great investments in technological solutions and the main goal was to transform the processes of finance transferences into a very quick way and reduce the costs with salaries. As a consequence of this process the contact with clients became very impersonal. The view of knowing and evaluating the customers started right after the implantation of the Brazilian Real Plan was initiated after and beginning of the process of reduction of the inflation indices and taxes of interests. In this environment appeared the union corporations that work among doctors and belong to Unicred System, institutions that in last fifteen years comes conquering spaces in niches, that previously were exclusive for banks in commercial field and that encloses 129 cooperatives in Brazil. This paper presents an study about Unicred of Fortaleza, involving its controllers e cooperated clients, beyond the controllers of the Unicred Porto Alegre, Unicred of Southwestern Goias, Unicred of Southern Rio de Janeiro, Unicred Middle Plateaus and Unicred Saint Carlos, what are the only ones in Unicredâs System that work exclusively in the niche of doctors and their relatives. The work identify, in the perspective of the involved companies: the reasons from what doctors decided to belong to Unicred and maintain financial relationship with it, although all sort of financial institutions that can be found in the market; the view that they have of the services provided by their business; the importance of the main tools of marketing relationship used to conquer and maintain the associated partners and focus the risks of the competition of the banks over the niches in what the Unicred system what on. The study contributes in terms of making a review of the concept that doctors, in function of the image of a joined and cooperative class, have a strong cooperative feeling, being this the main booster of the growth of Unicred System.